2000
DOI: 10.1016/s0736-5748(99)00069-6
|View full text |Cite
|
Sign up to set email alerts
|

Developmental maturation of the N‐methyl‐d‐aspartic acid receptor channel complex in postnatal rat brain

Abstract: The N-methyl-D-aspartate (NMDA) receptor plays an important role in developmental plasticity. Previous studies have reported differences between the NMDA receptor-channel complex in the rat pup brain and the adult brain. In the present study, modulation of the NMDA channel complex as a function of age was measured to determine when the temporal switching of the NMDA receptor from the immature form to the adult mature form takes place. [(3)H]MK-801 binding was measured in the rat forebrain from postnatal day 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 45 publications
0
28
0
3
Order By: Relevance
“…The accumulating evidence indicates that the various subunits (NR1, NR2A-D, NR3A) composing the native NMDA receptor channel undergo dramatic differential change during the first few weeks of the postnatal life in the rat (Dingledine et al 1999). It has been suggested that the NMDA receptor is not present in fully mature form until the second postnatal week in the rat (Sircar 2000). Thus, the pharmacological effects of NMDA antagonism in the infant may not necessarily be comparable to those in the adult.…”
mentioning
confidence: 99%
“…The accumulating evidence indicates that the various subunits (NR1, NR2A-D, NR3A) composing the native NMDA receptor channel undergo dramatic differential change during the first few weeks of the postnatal life in the rat (Dingledine et al 1999). It has been suggested that the NMDA receptor is not present in fully mature form until the second postnatal week in the rat (Sircar 2000). Thus, the pharmacological effects of NMDA antagonism in the infant may not necessarily be comparable to those in the adult.…”
mentioning
confidence: 99%
“…89 Neonatal sıçanlarda poliamin biyosentezinin durdurulmasının, erişkinlik evresinde özellikle serebellumda nöronal kayıplara neden olduğu belirlenmiştir. 90,91 Poliaminlerin sinir sisteminde bu tip önemli bir etkide bulunmalarının temelinde NMDAR ile etkileşimleri olduğu düşünülmektedir. Gelişim evresinde MSS'de poliamin miktarının en yüksek seviyesinde olduğu ve gelişim tamamlandı-ğında miktarının azaldığı tespit edilmiştir.…”
Section: Eksi̇totoksi̇si̇tede Nmdar Nfκb Ve Poli̇ami̇n İli̇şki̇si̇unclassified
“…Gelişim evresinde MSS'de poliamin miktarının en yüksek seviyesinde olduğu ve gelişim tamamlandı-ğında miktarının azaldığı tespit edilmiştir. 91 Gelişim döneminde NMDAR'nin de nöronal büyüme, hücre göçü ve sinaps oluşumunda etkili olması, poliaminlerin, NMDAR'yi düzenleyici işleve sahip olabileceklerini düşündürmektedir. 92 …”
Section: Eksi̇totoksi̇si̇tede Nmdar Nfκb Ve Poli̇ami̇n İli̇şki̇si̇unclassified
“…Çalışmamızda NMDA reseptör blokajı yaptığımız gelişim penceresi, NMDA reseptörlerinin tamamen olgun şekle dönüştüğü zaman dilimini kapsamaktadır (41). NMDA reseptör blokajının sinaps oluşumunun yoğun olduğu yeni doğan döneminde apopitoza bağlı nörodejenerasyona, yeni doğandanvpuberteye geçiş aşamasında minimal nörodejenerasyona ve puberteden sonra yetişkin dönem-de ise eksitotoksik nörodejenerasyona neden olduğu gösterilmiştir (42)(43)(44).…”
Section: şEkil 6 Morris Su Havuzu Bellek Testinde Yüzme Hızı (Cm/sn)unclassified